Characterisation of a new greenhouse model: With and without insect-proof screen - Santonicola, Luigi; Napolitano, Antonietta; Castelluccio, Francesco; Greco, Barbara; De Maio, Michele; Farina, Mario (Italian Journal of Agronomy, 2017)
A natural ventilation greenhouse is a patented new greenhouse model that maximises natural ventilation and allows stable installation of an anti-insect proof screen. The effects of the presence or absence of an anti-insect proof screen are compared with various parameters of the soil [moisture, pH, electrical conductivity (EC), nitrates], of the greenhouse environment [irradiance, Hargreaves-Samani reference crop evapotranspiration (ETo)] and of the plants [fresh matter, dry matter, leaf area index (LAI)]. The presence of the insect-proof screen reduces the water requirements of tomato. Indeed, soil moisture, delivered water and ETo are significantly lower compared to the greenhouse without an insect-proof screen. An insect-proof screen also reduces the EC and nitrates in the soil, improves LAI, doubles the amount of fresh matter of plant parts and triples the fresh matter of the productive part with respect to a greenhouse without an anti-insect-proof screen.